Detection of Staphylococcal Enterotoxins A and E and Methicillin Resistance in Staphylococcus aureus Strains From Moroccan Broiler Chicken Meat - Sabrine Nacer; Saâdia Nassik; Fatima Zahra El Ftouhy; Sophia Derqaoui; Mohamed Mouahid; Mustapha Lkhider (International Journal of Food Science)
Foodborne epidemics have become a serious public health emergency worldwide. Foods of animal origin, in particular chicken meat, are considered to be potential vectors of pathogenic bacteria, particularly Staphylococcus aureus. This bacterium can be resistant in the form of methicillin-resistant S. aureus (MRSA) or produce enterotoxins leading to food poisoning when ingested. This study is aimed at exploring the virulence genes in S. aureus responsible for producing enterotoxins (staphylococcal enterotoxin [SE] A [sea] and SE E [see]) and determining the prevalence of MRSA in raw broiler meat in the Casa-Rabat region in Morocco. A quantitative (q) PCR (qPCR) assay, using specific primers for S. aureus (nuc) confirmation and detection of enterotoxin genes (sea and see), as well as the methicillin-resistant gene (mecA), was employed. Our findings indicated that all tested strains were positively identified as S. aureus. Among them, one isolate (1/54) tested positive for the see gene (1.85%), while none carried the sea gene. Furthermore, the mecA gene, indicative of MRSA, was present in 12/54 of the isolates (22.22%). The potential presence of MRSA in Moroccan poultry meat underscores a public health risk. Thus, stringent measures are imperative to curtail the contamination and proliferation of this bacterium during the slaughtering process, underscoring the importance of continuing research into the prevalence of MRSA colonization among poultry slaughterhouse personnel.